Russian Federation : Technical Note on Crisis Management and Crisis Preparedness Frameworks. (IMF Staff Country Reports; Country Report, 2011)
This technical note discusses the lessons learned from the financial crisis in Russia in 2008. The note summarizes key findings and recommendations, and analyzes the institutional framework and coordination arrangements for systemic risk monitoring and crisis management. It also covers crisis management tools, deals with legal protection, and assesses crisis prevention measures including approaches to intervene with potential problem institutions at an early stage.